Assessment of Incidence of Superbugs and Antibiotic Resistance in Orthopaedics, A Cross-Sectional Study (Journal of Pakistan Orthopaedic Association, 2023)
Objectives: Due to the presence of metallic implants, orthopedic surgeries are at increased risk of microbiological contamination and infection. Such infections require aggressive and prolonged use of antimicrobial therapy. The objective of our study is to determine the frequency of growth in cultures and identify patterns of new antibiotic resistance from culture growth of infected implant patients.Methods: Total 188 patients were included in this study which was conducted in Liaquat National Hospital from July 2022 till July 2023. Suspected infections were confirmed biochemically when ESR ?30mm/hour or CRP ?10 mg/dl. Such patients underwent routine surgeries for infection eradication as per routine orthopaedic guidelines. Appropriate body tissue specimens were sampled for culture and sensitivity. Descriptive statistics were calculated.Results: There were 64.4% male and 35.6% female patients. Mean age was 43.61±14.21 years. Mean ESR and CRP was 63.89±34.92 mm/hour and 6.11±4.54 mg/dl respectively. In 23.9% previous surgical procedure was ORIF. In our study, 87.8% of patients were found with culture growth while most common culture bacterium was MRSA found among 40.6% patients. Most sensitive antibiotic was Vancomycin (67.3%). 13.2% of patients showed no growth indicating significant covert or indolent bacteria.Conclusion: Culture growth was observed in 87.8% patients with MRSA being the most common organism. Vancomycin was found as most sensitive antibiotic.